Synergistic antibacterial mechanism of silver-copper bimetallic nanoparticles - Hao, Zhaonan; Wang, Mingbo; Cheng, Lin; Si, Minmin; Feng, Zezhou; Feng, Zhiyuan (Frontiers in Bioengineering and Biotechnology, 2024)
The excessive use of antibiotics in clinical settings has resulted in the rapid expansion, evolution, and development of bacterial and microorganism resistance. It causes a significant challenge to the medical community. Therefore, it is important to develop new antibacterial materials that could replace traditional antibiotics. With the advancements in nanotechnology, it has become evident that metallic and metal oxide nanoparticles (MeO NPs) exhibit stronger antibacterial properties than their bulk and micron-sized counterparts. The antibacterial properties of silver nanoparticles (Ag NPs) and copper nanoparticles (Cu NPs) have been extensively studied, including the release of metal ions, oxidative stress responses, damages to cell integrity, and immunostimulatory effects. However, it is crucial to consider the potential cytotoxicity and genotoxicity of Ag NPs and Cu NPs. Numerous experimental studies have demonstrated that bimetallic nanoparticles (BNPs) composed of Ag NPs and Cu NPs exhibit strong antibacterial effects while maintaining low cytotoxicity. Bimetallic nanoparticles offer an effective means to mitigate the genotoxicity associated with individual nanoparticles while considerably enhancing their antibacterial efficacy. In this paper, we presented on various synthesis methods for Ag-Cu NPs, emphasizing their synergistic effects, processes of reactive oxygen species (ROS) generation, photocatalytic properties, antibacterial mechanisms, and the factors influencing their performance. These materials have the potential to enhance efficacy, reduce toxicity, and find broader applications in combating antibiotic resistance while promoting public health.